Assessment of the Diffuse Attenuation Coefficient of Photosynthetically Active Radiation in a Chilean Lake - Rodríguez López, Lien.; González Rodríguez, Lisdelys.; Durán Llacer, Longel.; García, Wirmer; Cárdenas, Rolando; Urrutia, Roberto (MDPI, 2022)
The diffuse attenuation coefficient of photosynthetically active radiation is an important inherent optical property of the subaquatic light field. This parameter, as a measure of the transparency of the medium, is a good indicator of water quality. Degradation of the optical properties of water due to anthropogenic disturbances is a common phenomenon in freshwater ecosystems. In this study, we used four algorithm-based Landsat 8 OLI and Sentinel-2A/B MSI images to estimate the diffuse attenuation coefficient of photosynthetically active radiation in Lake Villarrica located in south-central Chile. The algorithms’ estimated data from the ACOLITE module were validated with in situ measurements from six sampling stations. Seasonal and intralake variations of the light attenuation coefficient were studied. The relationship between the diffuse attenuation coefficient of photosynthetically active radiation, meteorological parameters, and an optical classification was also explored. The best results were obtained with QAA v6 KdPAR Nechad (R2 = 0.931, MBE = 0.023 m−1, RMSE = 0.088 m−1, and MAPE = 35.9%) for spring and QAA v5 Kd490 algorithms (R2 = 0.919, MBE = −0.064 m−1, RMSE = −0.09 m−1, and MAPE = 30.3%) for summer. High KdPAR values are associated with the strong wind and precipitation events suggest they are caused by sediment resuspension. Finally, an optical classification of freshwater ecosystems was proposed for this lake. The promising results of this study suggest that the combination of in situ data and observation satellites can be useful for assessing the bio-optical state of water and water quality dynamics in Chilean aquatic systems
Keywords: Secchi disk optical depth; Diffuse attenuation coefficient; Landsat and sentinel images; Lake Villarrica; Chile